EXCELLENCE IN CUSTOMER SERVICE: the importance of quality in services - Lacerda, Maria Izabela Silva de; Casagrande, Diego José (Revista Interface Tecnológica, 2022)
The main objective of this work is to present the importance of quality in customer service and what can impact it, because only through quality can organizations achieve excellence to remain competitive in the market and ensure success. For this, the methodology used for the elaboration of this article was the bibliographic research, consultation in books, articles, magazines, among others. Today, with more rigorous and cautious customers, quality has become essential for companies that seek to meet their needs, especially in customer service, as there is no point in providing high quality products if the service is of poor quality, this will cause companies to lose customers. Despite being crucial, quality alone is no longer a competitive differential and does not always guarantee success for companies, it is necessary that they constantly seek excellence in service through the quality of their services, continually training employees, creating improvement programs and carrying out customer satisfaction surveys, in this way they will be able to guarantee a differential in their services, the full fulfillment of the needs, desires and expectations of their customers, and success.